Impact of Accounting Information on Financial Statements to the Stock Price of the Energy Enterprises Listed on Vietnam’s Stock Market - Hung, Dang Ngoc; Ha, Hoang Thi Viet; Binh, Dang Thai (International Journal of Energy Economics and Policy, 2018)
This paper studies the impact of accounting information on financial statements to the stock price of energy enterprises listed on Vietnam’s stock market. By using the OLS regression model and quantile regression model (QR), the author studies the influence of factors such as return on assets (Roa), capital structure (LV), enterprise size (Size), current ratio (CR), and accounts receivable turnover (Turnover) to stock prices. Data from this study were collected from 44 energy enterprises during 2006-2016. The results show that return on assets (Roa), enterprise size (Size), current ratio (CR), and accounts receivable turnover (Turnover) are positively correlated with the stock price, with an explanation level of 48.47%. Capital structure (LV) does not affect stock prices. Based on the research results, the authors propose some recommendations for investors and enterprises and suggest other research directions as well as adding new factors to the stock price. Keywords: accounting information; financial statement; stock price; energy enterprises JEL Classifications: E44, G2, Q43